Preliminary evidence on the diagnostic value of apolipoprotein B and A-I in peripheral artery disease among Vietnamese patients with diabetes - Ha, Nguyen Manh; Lan, Nguyen Thi Ho; Binh, Pham Thai; Phuc, Vu Minh; Kien, Hoang Van; Quynh, Tran Thi Nhu; Quynh, Nguyen Thi Nhu; Giang, Nguyen Thi; Thu, Nguyen Thi; Thu, Nguyen Thi Minh; Mai, Nguyen Ngoc; Hoa, Nguyen Thi Ngoc; et al. (Tạp chí Nghiên cứu Y học, 2024)
To evaluate the value of apolipoprotein A-I, B, and the apoB/AI ratio in the diagnostic of peripheral artery disease among patients with diabetes, we conducted a cross-sectional study of which they underwent clinical evaluation, standardized Doppler ultrasound and blood test. Area under the Receiver Operating Characteristic curve method was employed to estimate the discriminatory ability of apolipoprotein A-I, apolipoprotein B, and the ApoB/A-I ratio. A total of 159 patients were included. ApoA-I, ApoB, and the ApoB/A-I ratio show statistically significant associations with most clinical and Doppler ultrasound characteristics of PAD. In Pearson’s correlation analysis, apolipoproteins showed a stronger correlation with ABI than the traditional lipid profile. The AUROC was 0.714 (95%CI: 0.635 - 0.794); 0.300 (95%CI: 0.219 – 0.380) and 0.604 (95%CI: 0.516 – 0.692) for apoB/A-I ratio; apoAI and apoB, respectively. The probability apoB/A-I cutoff of 0.666 had a sensitivity of 0.682 and a specificity of 0.662. Apolipoprotein AI and Apolipoprotein B are tests with considerable potential in diagnosing peripheral arterial disease in patients of type 2 diabetes mellitus patients. Further studies are needed with larger sample sizes, and employing imaging diagnostic modalities with higher reliability as the gold standard (MSCT angiography).